Pengembangan Strategi Komunikasi Digital Marketing Probetech Dalam Membangun Brand Awareness Melalui Instagram - Raisha Maharani; Alfa Taufan Latif; Fikry Fachrurrizal (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to develop a digital marketing communication strategy for Probetech in building brand awareness through Instagram. Probetech is a company engaged in occupational safety and health (K3) inspection and testing services that recently established itself as an independent brand and faces challenges in strengthening its brand identity in the digital environment. This research used a descriptive qualitative approach through observation, interviews, active participation, documentation, and literature study. SWOT analysis was applied to identify the conditions of Probetech’s Instagram account, while the Integrated Marketing Communication (IMC) concept was used as the main theoretical foundation in formulating the strategy. The results show that the development of the “Probetech Safety Insight” campaign, supported by content pillars, visual guidelines, and content planning, was able to create a more structured and consistent communication direction. The strategy emphasizes educational content, visual consistency, and integrated communication to strengthen the company’s professional image and credibility. The implementation guideline developed in this study also functions as a practical reference for maintaining sustainable brand communication through Instagram.